Share class structure and the efficiency of corporate takeover : an experiment - Tan, Alicia Yan Xiu (2019)
This research paper tests the theoretical conclusions of Grossman and Hart (1988) through a laboratory experimental approach. Six treatment variations were designed to study the efficiency of management under three dimensions: share structures (one-share-one-vote and dual-class share structure), the presence of an open market and the use of proration. The experiment was conducted through a computerised asset market using a continuous double auction and unrestricted and restricted tender offer market. Through the trading game, the Incumbent and Raider battled for the control of the firm. Our experiment results were not in line with our hypothesis. From our experiment, we obtain these results: (i) Number of successful tender offers were independent on share structure, (ii) In the presence of a market, there were fewer successful tender offers and (iii) Proration results in a significantly lower percentage of successful tender offers by the efficient Raider in a dual class share structure compared to a one-share-one-vote share structure.